The Effectiveness of P5 Project-Based E-Modules on the Learning Independence of Grade IV Students of SDN 3 Silanca - Gloria Tri Andini Tagentju; Arif Firmansyah; Muchdar Muchdar; Herlina Herlina; Muslim Muslim (FKIP - Universitas Riau, 2026)
This study aimed to determine the effectiveness of a P5 project-based e-module in improving the learning independence of fourth-grade elementary school students. A pre-experimental one-group pretest–posttest design was employed involving nine students at SDN 3 Silanca. The learning intervention was implemented over four meetings using a P5 project-based e-module. Data were collected through a learning independence questionnaire based on Zimmerman's Self-Regulated Learning theory, measuring learning initiative, responsibility, decision-making, self-confidence, time management, and self-evaluation. The instrument was validated and demonstrated high reliability. Data were analyzed using descriptive statistics, the Shapiro–Wilk test, the Paired Sample t-Test, and the N-Gain test. The results showed that the mean score increased from 63.00 to 81.00. The Paired Sample t-Test indicated a significant improvement (p < 0.05), while the N-Gain analysis showed moderate effectiveness. The findings indicate that the P5 project-based e-module effectively promotes learning independence and can serve as an innovative digital learning resource to support the implementation of the Merdeka Curriculum in elementary schools.